Four release tests exhibit variable silver stability from nanoparticle-modified reverse osmosis membranes. (15th October 2018) - Bi, Yuqiang; Han, Bingru; Zimmerman, Sean; Perreault, Francois; Sinha, Shahnawaz; Westerhoff, Paul
Abstract: Modification of polyamide reverse osmosis (RO) membranes with silver nanoparticles (AgNP) may effectively control biofouling. While silver leaching tests are usually performed during membrane development, the lack of common testing protocols limits cross-comparison among different labs. We compare four release tests to quantify the release of dissolved and nanoparticulate silver from polyamide RO membranes prepared through in situ surface functionalization: (1) batch immersion, (2) dead-end filtration, (3) cross-flow filtration, and (4) low-pressure water jetting. For the first time, we demonstrated the possibility of AgNP release to membrane-treated water through direct AgNP detachment. When using Nanopure water as an extraction solution, water jetting resulted in the fastest silver mass release, while dead-end filtration caused the slowest release based on the initial release kinetic data. Dead-end filtration exhibited silver mass release an order of magnitude lower than the other three tests. Although cross-flow filtration may best represent the RO membrane operation, quantifying silver release suffers from poor mass balance due to the adsorption of dissolved silver by various reactor components and large volumes of water usage. A commonly applied batch immersion method was low cost and easily performed, but may not induce hydraulic shear sufficient for AgNP detachment from a RO membrane. The information on silver release behavior may depend on the specific test, which is important for assessing antimicrobial efficacy and service life of the nanoparticle-functionalized membranes. Highlights: Four release test systems were applied to silver nanoparticle (AgNP) coated RO membranes. The majority of silver released was ion rather than nanoparticles. Rates and extent of silver release varied across four testing platforms. Dead-end filtration platform released the lowest silver mass.